2021
DOI: 10.1177/0271121420988890
|View full text |Cite
|
Sign up to set email alerts
|

It’s About Time! Advancing Justice Through Joyful Inquiry With Young Children

Abstract: Young learners often are enchanted with the world, fascinated by the ordinary, and absorbed in the present moment. We explore interconnected ideas about how young children’s natural proclivity toward being curious, and noticing differences among people should be harnessed toward socially just ends. We consider ways in which joyfulness in learning are preserved, as teachers partner with young learners to cultivate their sense of justice in the classroom and beyond. We use disability studies in education as a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Furthermore, when children gain positive emotions in Anji Play, it eventually leads to more active participation and reflection in playing by the children themselves, in which they can improve their ability to acquire knowledge. This has double-win implications [32]. Young children also experience positive emotional consequences when they engage in prosocial behaviors in Anji Play [33].…”
Section: Providing Opportunities For Children To Reflect and Share Af...mentioning
confidence: 99%
“…Furthermore, when children gain positive emotions in Anji Play, it eventually leads to more active participation and reflection in playing by the children themselves, in which they can improve their ability to acquire knowledge. This has double-win implications [32]. Young children also experience positive emotional consequences when they engage in prosocial behaviors in Anji Play [33].…”
Section: Providing Opportunities For Children To Reflect and Share Af...mentioning
confidence: 99%
“…While we commonly hear phrases like anti-bias education, equity-based practices, anti-racist pedagogy, and equitable learning, data from Cycle 1 of this study showed that several early childhood teachers connected different meanings to many of these terms (Escayg, 2019). If schools are to engage early learners in critical discourse and help build their equity-oriented vocabularies, teachers must first make sure they are in agreement on how they define critical social justice terms in their unique context (Erwin et al, 2021).…”
Section: Shared Language For Educators and Early Learnersmentioning
confidence: 84%
“…Trust can be built with sessions of critical discourse. A series of critical discourses wherein educators are able to share their own experience and speak their truth promotes equity-oriented learning (Erwin et al, 2021;Singleton et al, 2006). These claims held true in both cycles of research, with participants describing their shared feedback as integral to their learning.…”
Section: Consistent Collaboration With Inclusive Feedbackmentioning
confidence: 99%